ASME 2010 International Manufacturing Science and Engineering Conference, Volume 1 2010
DOI: 10.1115/msec2010-34145
|View full text |Cite
|
Sign up to set email alerts
|

Optimization on the Production of Variable Thickness Aluminium Tubes

Abstract: The variable thickness tube drawing is a new modification in the tube drawing methods which enables production of axially variable thickness tubes faster and easier in comparison with other similar methods like radial forging or indentation forging. The production of this type of tubes can be used in optimum design of mechanical parts which do not necessarily need constant thickness along the axis of tube and this method can strikingly reduce the overall weight of parts and mechanical assemblies like cars. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Bihamta et al (2010a) presented numerical studies of variable wall thickness aluminium tubes using finite element method. Bihamta et al (2010b) optimized the production of variable wall thickness aluminium tubes and evaluated effect of tube initial geometry on the minimum possible final thickness. Komori (2003) reported that in sheet metalworking processes, the forming limit diagram indicates the combination of major and minor in-plane strains beyond which necking or fracture occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bihamta et al (2010a) presented numerical studies of variable wall thickness aluminium tubes using finite element method. Bihamta et al (2010b) optimized the production of variable wall thickness aluminium tubes and evaluated effect of tube initial geometry on the minimum possible final thickness. Komori (2003) reported that in sheet metalworking processes, the forming limit diagram indicates the combination of major and minor in-plane strains beyond which necking or fracture occurs.…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of tubes were studied in the recent works by Guillot et al (2010) and Bihamta et al (2010b) for the automobile and bicycle industries. The variable thickness tube drawing process is a modification in the tube drawing methods which enables production of axially variable wall thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…However, their area reduction limits were always about 40%; (iv) The drawing stress ratios are about 3.38 and 3.73 for AA6063-O and AA6063-T4 tubes respectively. These values can be considered as forming limit criterion which is used to optimize the variable wall thickness tube drawing process as reported in the work of Bihamta et al [12].…”
Section: Resultsmentioning
confidence: 99%
“…The method proposed in this paper determines the drawing limit for each tube dimension with just one experiment. The position controlled plug technique was recently proposed for producing variable wall thickness tubes [11][12][13]. In this paper, the same principle of position controlled plug technique was used.…”
Section: Introductionmentioning
confidence: 99%
“…Bihamta et al [8] studied state of residual stresses in the variable thickness tubes. Bihamta et al [9] developed an optimization procedure coupled with a finite element method (FEM) to study design specifications of this process. Bihamta et al [10] studied effect of tube initial geometry on the minimum and maximum possible thicknesses in the production of variable thickness tubes using numerical and experimental.…”
Section: Introductionmentioning
confidence: 99%